Effect of extracellular vesicles on cancer cell lines in vitro and biodistribution in an ectopic osteosarcoma mouse model - Abello, Javier (Kansas State University, 2018)
Human umbilical cord-derived mesenchymal stromal cells (HUC-MSCs) have an enormous therapeutic potential because of their immunomodulatory and anti-inflammatory properties. However, there are limitations for their therapeutic use due to low cell survival after implantation, the risk of culture-borne pathogens, and the risk of embolism and thrombosis after intravenous infusion. Exosomes, on the other hand, constitute an important part of the MSCs secretome and may play a role in their therapeutic effects. Here, it was demonstrated that HUC-MSC-derived exosomes accumulate in human and mouse osteosarcoma cell lines in vitro and reduce their proliferation. The distribution of HUC-MSCs exosomes was shown in osteosarcoma tumor-bearing mice. Exosome distribution in vivo was observed using Magnetic Resonance Imaging (MRI) of gadolinium-labeled exosomes and by fluorescent imaging after infusion of near infrared dye-labeled exosomes. HUC-MSC exosomes accumulated in the tumor throughout the 48 hours post-injection period. In contrast, synthetic lipid nanoparticle accumulates in tumor only for the first 3 hours post-injection. In summary, this study showed that HUC-MSCs exosomes can accumulate to osteosarcoma cells in vitro and in vivo, and thus they may be useful for detecting cancer metastasis.
Keywords: Extracellular vesicles; Mouse osteosarcoma model; Gadolinium nanoparticle